2013
DOI: 10.1074/jbc.m113.454421
|View full text |Cite
|
Sign up to set email alerts
|

NemR Is a Bleach-sensing Transcription Factor

Abstract: We demonstrate a bleach-sensing bacterial response system and a new mechanism contributing to bacterial bleach survival. Hypochlorous acid (HOCl), the active component of household bleach, also functions as a powerful antimicrobial during the innate immune response. Despite its widespread use, surprisingly little is known about how cells sense or respond to HOCl. We now demonstrate that Escherichia coli NemR is a redox-regulated transcriptional repressor, which uses the oxidation status of HOCl-sensitive cyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
155
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(161 citation statements)
references
References 40 publications
(102 reference statements)
6
155
0
Order By: Relevance
“…Divergent expression from the same promoter is commonly observed in genes that are negatively regulated by Tet repressors (16). Examples of TetR homologues involved in resistance to biocides are QacR in Staphylococcus aureus and EnvR and NemR in Escherichia coli (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Divergent expression from the same promoter is commonly observed in genes that are negatively regulated by Tet repressors (16). Examples of TetR homologues involved in resistance to biocides are QacR in Staphylococcus aureus and EnvR and NemR in Escherichia coli (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that MGO accumulates in RCS-stressed E. coli as part of a pathway facilitating production of polyphosphate, a biopolymer that prevents the aggregation of oxidized proteins (4). It is therefore not surprising that both NemA and GloA are necessary for HOCl survival in E. coli (3).…”
mentioning
confidence: 99%
“…To survive RCS exposure, Escherichia coli mounts a complex and still incompletely understood stress response that is coordinated by several different transcriptional regulators (2). These are distinct from the transcription factors that sense reactive oxygen species (ROS) and include the repressor NemR (2,3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These include the chaperone Hsp33, which in its active state prevents irreversible aggregation of proteins, and the regulators NemR, HypR, and HypT, which in turn regulate genes that support survival of the stress (6 -10). Whereas Hsp33, NemR, and HypR are activated by oxidation of cysteine thiols (7,8,11), HypT is activated by HOCl by simultaneous oxidation of three methionines (Met-123, Met-206, and Met-230) to methionine sulfoxide, thus forming the active HypT species (10). This active state can be mimicked by methionine-to-glutamine substitution, leading to the constitutively active mutant HypT M123,206,230Q (10).…”
mentioning
confidence: 99%